Adaptation patterns of sixteen alfalfa (Medicago sativa L.) cultivars across contrasting environments of Algeria and implications for the crop improvement - Achir, Chahira; Annicchiarico, Paolo; Pecetti, Luciano; Khelifi, Houssem-Eddine; M'Hammedi-Bouzina, Mahfoud; Abdelguerfi, Aissa; Laouar, Meriem (Italian Journal of Agronomy, 2020)
The additive main effects and multiplicative interaction analysis was applied to assess the genotype × environment interaction (GEI) effects and stability for 4-year dry matter yield (DMY) of 16 alfalfa (Medicago sativa L.) cultivars of diversified geographic origin grown in four Algerian environments given by the combination of two water managements (rainfed and irrigated) and two evaluation sites, viz. the sub-humid location of Alger and the semi-arid, salinity-affected site of Hmadna. The analysis of variance (ANOVA) revealed significant variation among cultivars and environments (P<0.001). The GEI was significant (P<0.001) and the environment main effect had greater influence than the genotype effect on long-term yield according to ANOVA. Rainfed conditions had 41.6% and 48.5% lower yield than the irrigated ones in Alger and Hmadna, respectively. Alfalfa cropping in the semiarid location caused lower DMY than in the sub-humid one (– 38.0% under irrigated and –45.2% under rainfed conditions) and a slightly lower persistence over the 4-year period. Outstanding environment-specific cultivar responses were observed, fully justifying the large GEI effects, although the Italian cultivar Sicilian ecotype had remarkable yield stability and good mean yield. The American variety Ameristand 801S and the Moroccan landrace Erfoud 1 were the most salt-tolerant cultivars. The evaluated germplasm, and particularly some exotic cultivars, could be used as parents to breed new varieties more adapted to drought and salinity in the Mediterranean basin.